Urbanization and its relationship with urban heat island in Tuxtla Gutiérrez, Chiapas - Zavaleta-Palacios, Mariana; Díaz-Nigenda, Emmanuel; Vázquez-Morales, Williams; Morales-Iglesias, Horacio; Narcizo de Lima, Gabriela (Ecosistemas y Recursos Agropecuarios, 2020)
Land use change is one of the most complex problems observed as part of the urban expansion process. It generates different consequences such as the Urban Heat Island (UHI) development. With the objective of identifying the presence of UHI in Tuxtla Gutiérrez, Chiapas, MM5 meteorological model was implemented to simulate the meteorological conditions for April 30th to May 6th, 2017. Considering the atmospheric conditions over the study area, the UHI was represented at different times of May 3rd, 2017. The results show the formation of the UHI over the city at different hours during the day. The UHI intensity varies from 0.5 to 2.5 ◦C but, it could be higher than 5 ◦C. The UHI affects mainly the center of the city as a consequence of factors such as soil properties, heat fluxes, and the geomorphological characteristics of the study area. Furthermore, considering the actual growth of the city, land use change was simulated. In some cases, the results show a bigger area and a higher intensity of the UHI phenomenon. Therefore, the presence of the UHI in the city is showed and the importance of the protection and conservation of green areas is indicated, which points out that UHI studies should be considered as part of territory planning for urban development.